CpG Methylation patterns in the IFN promoter in naive T cells: Variations during Th1 and Th2 differentiation and between atopics and non-atopics - White, Greg; Hollams, E.; Yerkovich, S.; Bosco, A.; Holt, B.; Bassami, M.; Kusel, M.; Sly, P.; Holt, P. (Blackwell Publishing, 2006)
Interferon- (IFN) gene expression is tightly regulated in early life, and exaggerated negative control of IFN production in CD4+ T cells has been associated with risk for subsequent development of atopy. Recent studies have demonstrated hypermethylation of CpG sites in the IFN promoter in neonates, a mechanism which in mice leads to strong suppression of IFN gene transcription. In the present study, the methylation status of six CpG sites in the proximal promoter of the human IFN gene was determined by bisulphite sequencing. Cell populations studied were Th1 or Th2 polarized cell lines derived from neonatal and adult CD4+/CD45RA+ T cells, CD4+ and CD8+ naive T cells from cord blood of children followed to outcome age 2 for assessment of atopy status, and CD4+ and CD8+ naive T cells from 6 yr old and adult atopics and controls. We demonstrate that in vitro differentiation of CD4+ T cells down the Th1 pathway (but not the Th2 pathway) is accompanied by progressive demethylation of CpG sites in the IFN promoter, which is most marked in neonatal cells. Atopy development by age 2 was not associated with variations in methylation patterns in cord blood T cells. However, IFN promoter methylation was reduced in CD8+ T cells from atopic children in the age range in which hyperproduction of IFN as recently been identified as a common feature of the atopic phenotype. The findings demonstrate the potency of IFN promoter methylation as a mechanism for control of human IFN gene expression, particularly during early life. Differential regulation of IFN promoter methylation in T cells may be an important contributory factor in atopy development in childhood, and this possibility warrants further detailed investigation.